The relationship between sense of direction, navigation familiarity, spatial anxiety, spatial visualisation and wayfinding information system of a visitors' wayfinding experience in a complex environment - Shamsuddin, Nik Atilla Atasha (2024)
This research explored the relationship between the sense of direction, navigation familiarity, spatial anxiety, spatial visualisation, and the wayfinding information system of visitors’ wayfinding experiences in the complex environment of Universiti Teknologi MARA, Puncak Alam Campus, Selangor. Challenges in navigating spatial environments were often found to reduce the relationship of elements such as area familiarity, anxiety about orientation, proficiency in spatial visualisation, and the use of signs or wayfinding aids. The research was driven by six objectives: (1) to investigate the potential disparities in sense of direction, navigation familiarity, and spatial anxiety based on demographics (gender) differences, (2) to examine the variations in sense of direction, navigation familiarity, and spatial anxiety in relation to demographics (age group, income classification, geographic location, employment status, and current occupation), (3) to establish the correlation between sense of direction scale and spatial visualisation ability scores among visitors, (4) to identify the interrelationships among visitors’, their spatial anxiety levels, Spatial Visualisation ability scores and wayfinding information system scores, (5) to explore the depth and scope of differences in sense of direction, spatial anxiety, Spatial Visualisation ability scores and wayfinding information, taking demographics into consideration, and (6) to identify the navigational experiences of individuals at the UiTM Puncak Alam campus. A sample of 150 visitors, comprising 61 males and 89 females, participated in the study. Utilising a quantitative method, participants were subjected to a navigation task and a survey. A significant finding was that many participants reported getting lost during their navigation of the campus, which might hint at challenges such as complex building layouts or insufficient signage. Additionally, a substantial number of participants voiced difficulties during wayfinding, indicating potential issues with the campus's wayfinding system, such as unclear signage or unfamiliarity with the layout. Conversely, a smaller group expressed satisfaction with their navigation experience, suggesting the adequacy of the existing wayfinding system and their personal navigation abilities. Gender appeared not to influence the sense of direction, indicating equal navigation task proficiency across genders. Age seemed to play a role in navigation familiarity, with age-related factors such as exposure and comfort potentially being influential. No clear connection was found between the sense of direction and spatial visualisation abilities. Moreover, having a high spatial visualisation ability did not guarantee reduced spatial anxiety. Interestingly, demographic attributes including gender, age, income, location, employment status, and occupation did not significantly affect aspects such as sense of direction, spatial anxiety, or spatial visualisation abilities. This research may contribute to the aspects of the wayfinding industry and policymakers to achieve the Sustainable Development Goals (SDGs) which aspire to provide everyone with access to a safe, affordable, accessible, and environmentally friendly wayfinding information system.